A new computer-aided tolerance analysis and optimization framework for assembling processes using DP-SDT theory. Issue 5 (September 2016) - Li, Hai; Zhu, Haiping; Zhou, Xuan; Li, Peigen; Yu, Zhiqiang
Abstract Tolerance analysis is frequently used in predicting the product quality and balancing the design tolerances in mechanical assemblies. Generally, the tolerance analysis procedure is rather complex and cumbersome, and the existing computer-aided tolerance analysis methods are insufficient in dealing with some assembly information and user-defined quality requirements. This paper presents a new comprehensive tolerance analysis and optimization framework using deviation propagation and small displacement torsor (DP-SDT) theory. In this framework, four modules are designed to model the tolerances, analyze the assembly processes, predict the product quality, and optimize the tolerances respectively. Comparing with the existing methods, this framework can better support the complex assembly information like 3D dimensional tolerances, geometric dimensioning and tolerancing (GD&Ts), different tolerance zones, geometric information, assembly sequence, and various kinds of locating modes. And more practical quality requirements besides the distance precisions can be analyzed. The framework is a helpful supplement in tolerance analysis field. An application prototype using the framework has been developed for SolidWorks, and a tolerance optimization example of lathe saddle is provided to verify the performance of the framework.